2012
DOI: 10.1038/ni.2427
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of IL-17-mediated signaling and inflammation by the ubiquitin-specific protease USP25

Abstract: Interleukin 17 (IL-17) plays an important role in infection and autoimmunity; how it signals remains poorly understood. In this study, we identified ubiquitin-specific protease 25 (USP25) as a negative regulator of IL-17-mediated signaling and inflammation. Overexpression of USP25 inhibited IL-17-triggered signaling, while USP25 deficiency resulted in increased phosphorylation of IκBα and Jnk, increased expression of chemokines and cytokines as well as prolonged half-life of Cxcl1 mRNA following IL-17 treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
160
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(164 citation statements)
references
References 50 publications
4
160
0
Order By: Relevance
“…Indeed, two deubiquitinating enzymes [DUB; the ubiquitin-specific protease USP25 and TNFAIP3 (also called A20)] were reported to be negative regulators of the IL-17-induced NF-kB cascade because they deubiquitinate TRAF6. 51,52 In addition, USP25 directly removes TRAF5 ubiquitination and consequently erases the signals for the TRAF5-dependent mRNA stabilization pathways. 51 More recently, a study showed that another DUB [MCPIP1 (also named Regnase-1)] served as a negative regulator of IL-17 signaling.…”
Section: Il-17 Family Cytokine-mediated Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, two deubiquitinating enzymes [DUB; the ubiquitin-specific protease USP25 and TNFAIP3 (also called A20)] were reported to be negative regulators of the IL-17-induced NF-kB cascade because they deubiquitinate TRAF6. 51,52 In addition, USP25 directly removes TRAF5 ubiquitination and consequently erases the signals for the TRAF5-dependent mRNA stabilization pathways. 51 More recently, a study showed that another DUB [MCPIP1 (also named Regnase-1)] served as a negative regulator of IL-17 signaling.…”
Section: Il-17 Family Cytokine-mediated Signaling Pathwaysmentioning
confidence: 99%
“…51,52 In addition, USP25 directly removes TRAF5 ubiquitination and consequently erases the signals for the TRAF5-dependent mRNA stabilization pathways. 51 More recently, a study showed that another DUB [MCPIP1 (also named Regnase-1)] served as a negative regulator of IL-17 signaling. 53 Unexpectedly, its endoribonuclease but not its deubiquitinase activity was required for the suppression of IL-17 signaling.…”
Section: Il-17 Family Cytokine-mediated Signaling Pathwaysmentioning
confidence: 99%
“…The ubiquitin-specific protease USP18 plays a key role for T cells in the progres of differentiating into Th17 cells (5). USP25 could remove the Lys-63-linked ubiquitination in TRAF5 and TRAF6 mediated by Act1 and inhibit IL-17R signaling and inflammation (6).…”
Section: Th17 Cells Which Have Attracted Widespread Attention As a Smentioning
confidence: 99%
“…The proinflammatory cytokines TGF-b, IL-6, IL-1b, and IL-23 are essential to Th17 cell differentiation and function (1)(2)(3)(4). Several deubiquitinases (DUBs) or E3 ligases are important regulators of Th17 cell differentiation (5)(6)(7)(8). The orphan nuclear receptor RORgt is crucial for Th17 cell development, but the modulation of its stability remains uncharacterized (2,9).…”
mentioning
confidence: 99%